Shift in the structure of Lasius flavus (Hymenoptera, Formicidae) nest complexes under the influence of anthropogenic factors - Stukalyuk, Stanislav; Goncharenko, Igor (Pusat Sistematik Serangga, Universiti Kebangsaan Malaysia, 2020)
The structure of five Lasius flavus Fabricius, 1781 (yellow meadow ant) nest complexes with 33 to 211 nest mounds exposed to the anthropogenic impact of varying intensity was studied in 2001 and 2014 from four locations in Crimea. The study areas can be arranged in order of increasing intensity of anthropogenic impact as follows: the Chatyr-Dag Mountain (no impact, two nest complexes), arboretum near Simferopol city (low-intensity impact, moderate grazing, one nest complex), the outskirts of Kurtsy village (high-intensity impact, intensive grazing, ne nest complex), and Gagarinsky Park (critical level of intensity, draining, one nest complex). In 2001, mound measurements were taken from all nest complexes, divided into squares of 20 × 20 m. In 2014, mound measurements were taken from three out of five locations, namely the Chatyr-Dag Mountain (one nest complex), Kurtsy village, and Gagarinsky Park). In 2014, the nest complex in Gagarinsky Park was found to no longer exist. Other nest complexes underwent significant changes. Small nest mounds either disappeared or grew in size. The total nest volume did not change significantly or slightly increased. Therefore, this study concluded that grazing did not affect the ability of nest complexes to grow. The lowering of the groundwater table was found to be a critical factor. Nest complexes on the Chatyr-Dag plateau turned out to be 100 years of age, and other nest complexes were at the age of 40 to 80 years.